2014
DOI: 10.1016/j.jacc.2013.11.023
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Silencing of the Transcription Factor IRF5 Reprograms the Macrophage Phenotype and Improves Infarct Healing

Abstract: Objectives The aim of the study was to test wether silencing of the transcription factor Interferon Regulatory Factor 5 (IRF5) in cardiac macrophages improves infarct healing and attenuates post-MI remodeling. Background In healing wounds, M1➛M2 macrophage phenotype transition supports resolution of inflammation and tissue repair. Persistence of inflammatory M1 macrophages may derail healing and compromise organ functions. The transcription factor IRF5 promotes genes associated with M1 macrophages. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
192
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(201 citation statements)
references
References 40 publications
6
192
0
3
Order By: Relevance
“…Much attention has focused on vascular abnormalities in the pathogenesis of the delayed wound healing in diabetes (36)(37)(38). The observation that GM3S SNA treatment almost doubles CD31…”
Section: Discussionmentioning
confidence: 99%
“…Much attention has focused on vascular abnormalities in the pathogenesis of the delayed wound healing in diabetes (36)(37)(38). The observation that GM3S SNA treatment almost doubles CD31…”
Section: Discussionmentioning
confidence: 99%
“…The balance of M1 vs. M2 polarized macrophages has been shown to influence cardiac repair (56)(57)(58). Using rat and pig IR injury models, de Couto et al (59) showed that intracoronary infusion of CDC exosomes, but not inert fibroblast exosomes, reduced the number of CD68 + macrophages within infarcted tissue and modified the polarization state of macrophages.…”
Section: Macrophage Polarization By Cdc Exosomesmentioning
confidence: 99%
“…The continued dominance of M1 macrophages may accelerate and exacerbate ischemic infarction. 179 Courties et al 93 found that silencing IRF5 in M1 macrophages led to a strikingly suppressed progression of myocardial ischemia-induced necrosis and cardiac dysfunction caused by the downregulation of proinflammatory responses. These sophisticated molecular processes must be fully clarified.…”
Section: Interferon Regulatory Factormentioning
confidence: 99%